PREDICTION OF UNFAVORABLE OUTCOMES OF PREGNANCY BASED ON BIOCHEMICAL SCREENING IN TRIMESTER - I. O. Makarov; E. V. Yudina; E. I. Borovkova; I. V. Martynova; E. I. Kirpikova (IRBIS LLC, 2016)
This article reviews the objectives of combination biochemical screening of unfavorable outcomes of pregnancy in trimester I. The characterization of prenatal screening markers is given, for example, β-hCG (beta-human chorionic gonadotropin) and РАРР-А (pregnancy-associated plasma protein A). The international and national approaches to the algorithm of carrying out of prenatal screening and conceptualization about prediction of pregnancy complications based on results of biochemical screening of serum concentrations of β-hCG and PAPP-A, are reviewed